‘KULTUR’ OG ‘MØDE’: Gensyn med amerikanske akkulturationsstudier 1936-1963 - Veber, Hanne (Tidsskriftet Antropologi, 2007)
The author traces the conceptualization of culture contact that emerged in American anthropology in the early 20th century and became the focus of ample investigative initiatives in the decades before and after World War II – only to vanish into blue air in the 1960s, leaving barely a fingerprint in the textbooks of the 21st century. Based on the published reports from research seminars on acculturation in the 1930s and -50s, the author exposes the concepts of culture contact and change in the heyday of these studies and considers the problems they posed to the scholars. At the outset, fieldwork and the importance of a historical perspective had been stressed as the bases for understanding crosscultural dynamics. Yet, emphasis gradually shifted to synchronic functional studies, resulting in a ‘theoretical lag’, as some leading scholars saw it. Comparative research allowed the formulation of preliminary typologies, the major ones being ‘incorporation’, ‘assimilation’, ‘fusion’, and ‘compartmentalization’. From these typologies more specialized vocabulary developed. Scholars began to realize that the generalizations which emerged had to do with types of contact conditions rather than types of culture, but most of them hesitated to follow up on this point. They disagreed over the definition of culture as an autonomous system that a majority ascribed to, while dissidents felt that the idea of seeing culture as an entity independent of the human beings was counterproductive to analysis of processes of cross-cultural contact and change. The ambitious grand scale acculturation research plan gradually withered. It never attained a hypothesis or a paradigm sufficiently clear-cut to inspire continuing investigation. Some scholars had become aware that unequal power relations made a salient characteristic of contact situations and trajectories, but at the height of the Cold War, they hesitated to pursue this issue. Eventually the preoccupation with acculturation faded away, and scholars moved into other areas of anthropological research.